Explicit Stress Communication Facilitates Perceived Responsiveness in Dyadic Coping - Pagani, Ariela Francesca; Donato, Silvia; Parise, Miriam; Bertoni, Anna; Iafrate, Raffaella; Schoebi, Dominik (Frontiers in Psychology, 2019)
The present study was aimed at examining the role of explicit stress communication in the context of dyadic coping. The general aim of the present study was to test a) whether explicit communication of daily stressful events predicted relationship satisfaction and b) whether the perception of responsiveness in dyadic coping mediated the association between explicit stress communication and partners’ satisfaction. We analyzed daily diary data from 55 married couples and multilevel analyses suggested that, although explicit stress communication was not associated with relationship satisfaction, it predicted both partners’ responsiveness in dyadic coping behaviors. Finally, responsive dyadic coping behaviors mediated the relationship between explicit stress communication and relationship satisfaction. On the whole, our findings showed that perceived responsiveness in dyadic coping with daily stressors was facilitated by explicit stress communication and that this contributed to the effectiveness of dyadic coping behaviors in fostering partners’ relationship satisfaction. We discussed how the current study contributes to the understanding of the dyadic coping process and its contribution to partners’ satisfaction, underscoring the importance of communication skills.